Differences in progression by surgical specialty: a national cohort study. Issue 2 (9th February 2022) - Hope, Carla; Lund, Jonathan; Griffiths, Gareth; Humes, David
Abstract : The aim of surgical training across the 10 surgical specialties is to produce competent day 1 consultants. Progression through training in the UK is assessed by the Annual Review of Competency Progression (ARCP). Objective: This study aimed to examine variation in ARCP outcomes within surgical training and identify differences in outcomes between specialties. Design: A national cohort study using data from the UK Medical Education Database was performed. ARCP outcome was the primary outcome measure. Multilevel ordinal regression analyses were performed, with ARCP outcomes nested within trainees. Participants: Higher surgical trainees (ST3–ST8) from nine UK surgical specialties were included (vascular surgery was excluded due to insufficient data). All surgical trainees across the UK with an ARCP outcome between 2010 and 2017 were included. Results: Eight thousand two hundred and twenty trainees with an ARCP outcome awarded between 2010 and 2017 were included, comprising 31 788 ARCP outcomes. There was substantial variation in the proportion of non-standard outcomes recorded across specialties with general surgery trainees having the highest proportion of non-standard outcomes (22.5%) and urology trainees the fewest (12.4%). After adjustment, general surgery trainees were 1.3 times more likely to receive a non-standard ARCP outcome compared with trainees in trauma and orthopaedics (T&O) (OR 1.33, 95% CI 1.21 to 1.45, p=0.001). Urology trainees were 36% less likely to receive a non-standard outcome compared with T&O trainees (OR 0.64, 95% CI 0.54 to 0.75, p<0.001). Female trainees and older age were associated with non-standard outcomes (OR 1.11, 95% CI 1.02 to 1.22, p=0.020; OR 1.04, 95% CI 1.03 to 1.05, p<0.001). Conclusion: There is wide variation in the training outcome assessments across surgical specialties. General surgery has higher rates of non-standard outcomes compared with other surgical specialties. Across all specialties, female sex and older age were associated with non-standard outcomes.